Annealing of CoFeB/MgO based single and double barrier magnetic tunnel junctions: Tunnel magnetoresistance, bias dependence, and output voltage - FENG, GEN; FENG, JIA-FENG; VAN, DIJKEN SEBASTIAN; COEY, JOHN MICHAEL DAVID (American Institute of Physics, 2009)
Co40Fe40B20/MgO single and double barrier magnetic tunnel junctions (MTJs) were grown using target-facing-target sputtering for MgO barriers and conventional dc magnetron sputtering for Co40Fe40B20 ferromagnetic electrodes. Large tunnel magnetoresistance (TMR) ratios, 230% for single barrier MTJs and 120% for the double barrier MTJs, were obtained after postdeposition annealing in a field of 800 mT. The lower TMR ratio for double barrier MTJs can be attributed to the amorphous nature of the middle Co40Fe40B20 free layer, which could not be crystallized during postannealing. A highly asymmetric bias voltage dependence of the TMR can be observed for both single and double barrier MTJs in the as-deposited states and after field annealing at low temperature. The asymmetry decreases with increasing annealing temperature and the bias dependence becomes almost symmetric after annealing at 350??C. Maximum output voltages of 0.65 and 0.85 V were obtained for both single and double barrier MTJs, respectively, after annealing at 300??C, a temperature which is high enough for large TMR ratios but insufficient to completely remove asymmetry from the TMR bias dependence.
PUBLISHED
Keywords: Physics